ONTOLOGICAL ENGINEERING OF EDUCATIONAL PROGRAMS - Gennadievich Korneev, Dmitry; Samuilovich Gasparian, Mikhail; Anatolievna Kiselеvа Irina; Aleksandrovich Mikryukov, Andrey (Revista Inclusiones, 2019)
One of the key objectives of the current development stage of the education system is to improve the practical orientation of training for the contemporary labor market. It is possible to solve the specified problem only using innovative methods and means of creation of information and educational space with respect to formation and processing of the educational objects and the program services distributed in an educational network, and allowing carrying out flexibly processes of educational and methodical providing of educational activity. The aim of the study is to determine the possibilities of using the ontological approach to the construction of innovative automated education management systems, which include the construction of individual learning trajectories.